Avaliação experimental de um sistema de refrigeração cascata subcrítico com HFCs/C02 - Queiroz, Marcus Vinícius Almeida (2017)
This study evaluates the performance of a cascade system in subcritical operation using the pair R134a/R744, as an option to conventional systems in supermarkets, which usually uses R404A, or R22. The experimental apparatus consists of a variable speed reciprocating compressor for R744 and an electronic expansion valve that promotes direct evaporation of the CO2 inside a cold room (2,3m x 2,6m x 2,5m) to maintain the internal air temperature stable. The high-temperature cycle consists of a reciprocating compressor for R134a, an electronic expansion valve, and an air-cooled condenser. A plate heat exchanger, which is at the same time, the condenser for the R744 and evaporator to R134a completes the setup. During the experimental tests, two parameters were manipulated: The superheating degree of the R744, 5-15 K, and the R744 compressor operation frequency, 45-65 Hz. The cooling capacity values for R134a/R744 ranged between 4,30 ± 0,01 and 5,57 ± 0,02 kW, demonstrating an application to the cascade system under variable thermal load conditions. This operational flexibility also extends to the air temperature values established inside the cold room, being the lower value of -17,7 ° C and higher -0,8 ° C. In order to contribute to the improvement of the cooling processes, mainly about the energy efficiency, a drop-in has been made at the high- temperature cycle, which R134a refrigerant charge has been replaced by R438A. The comparison was done regard both systems providing similar cooling capacities and air temperature values inside the cold room. As a result, the consumption of the compressor operating with R438A was higher in all tests. The COP values for the R134a/R744 system ranged from 1,81 ± 0,01 to 2,09 ± 0,01, while with the R438A/R744 system, from 1,41 ± 0,01 to 1,66 ± 0,01. The total equivalent warming impact for the R438A/R744 system was higher compared to the original system, as a result of the higher GWP for the R438A and higher electrical power consumptions. It has been proven the proposed drop-in, at the high temperature cycle from R134a by R438A, is a less efficient choice for such specific applications.